PERFORMANCE AND COST BENEFIT OF REPLACING WHEAT OFFAL AT VARYING LEVELS WITH MAIZE OFFAL IN THE DIETS OF WEANER RABBIT - Adamu, O. M.; Egbo, M. L.; Doma, U.D.; Muhammad, A. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was conducted to evaluate the performance and cost implications of replacing wheat offal at varying levels with maize offal in the diets of weaner rabbits. The experiment was carried out at the Rabbitry Unit of the Department of Animal Production, Abubakar Tafawa Balewa University, Bauchi, Nigeria. Fifty (50) weaner rabbits were allotted in a Completely Randomized Design (CRD) to five dietary treatments (0, 25, 50, 75, and 100% maize offal inclusion) with three replicates of three rabbits each. The feeding trial lasted for eight weeks. Data were collected on feed intake, body weight gain, feed conversion ratio (FCR), mortality, and economic indices. Total feed intake ranged from 4.26 kg in diet 1 to 4.40 kg in diet 4, and daily feed intake from 76.06 g to 78.50 g. Daily weight gain ranged from 12.11 g in diet 5 to 13.36 g in diet 4, while FCR ranged between 5.50 in diet 3 and 6.71 in diet 1, showing no statistical differences (p value) among treatments. Mortality was very low, with only one death recorded in diet 1. cost analysis revealed that feed cost per kilogram ranged from ₦391.52 in diet 5 to ₦402.14 in diet 1,while total feed cost varied between ₦1,679.62 (diet 5) and ₦1,740.69 (diet 4). Total weight gain ranged from 0.68 kg (diets 2 and 5) to 0.75 kg (diet 4). Feed cost per kilogram gain was lowest in diet 4 (₦2,320.92) and highest in diet 2 (₦2,509.71), indicating better cost-effectiveness at higher maize offal inclusion. It was concluded that maize offal can completely replace wheat offal in the diets of weaner rabbits without adverse effects on growth performance while reducing feed cost per unit of weight gain. It is therefore recommended that maize offal be incorporated into rabbit diets as a cost-effective alternative to wheat offal, with potential to improve profitability and sustainability of rabbit production.